Deprivation and infant feeding at birth. (24th May 2012) - Ajetunmobi, O; Whyte, B
Abstract : Aim: To examine the association between the health services and increased breastfeeding rates observed in deprived areas. Methods: Registered births were linked to maternity, infant and child health surveillance records held by the Information Services Division, NSS Scotland. A total of 20, 338 and 6607 singleton births to first time mothers between 2003 and 2009 were linked in the most and least deprived areas (Scottish Index of Multiple Deprivation – SIMD 2006) respectively. Infant feeding was assessed at birth. Multiple births and infants who died within the first year of birth were excluded from the analysis. Descriptive and multivariate analysis (logistic regression – forwards and manual) was conducted using SPSS vs 17 and STATA vs 11. Results: There was an increase in any breastfeeding rates at birth (mixed and exclusive) observed in the most deprived areas from 41% in 2001 to 49% in 2009 compared to the least deprived areas which remained relatively stable (figure 1 ). Mixed feeding formed an important component of any breastfeeding in the most deprived areas (figures 2 and 3 ). However, the increasing trends were not evident when confounding factors were accounted for (p<0.05). A range of demographic, socio-cultural, maternal and infant health characteristics and features of the health system independently predicted the types and duration of any breastfeeding in the most deprived areas. In particular, older maternal age > 25 years, mother of non-British birth, maternal and paternal socio-economic status and maternal health/health behaviour influenced the observed trends in the deprived areas. A 'hospital effect' was also observed (table 1 ). Conclusion: The linked data set is an invaluable resource for exploring trends in deprived areas and highlights factors that promote breastfeeding in these areas. Increased breastfeeding rates observed in deprived areas can in part be attributed to changes in the composition of the population e.g. more mothers of non-British birth. In addition, a higher prevalence of mixed feeding over time reflects a shift in infant feeding patterns (and a possible process of acculturation). A number of factors influence the likelihood to provide any breast milk at birth underlining the importance of multi-factorial interventions to promote breastfeeding in deprived areas.